Facile fabrication of WS2 nanocrystals confined in chlorella-derived N, P co-doped bio-carbon for sodium-ion batteries with ultra-long lifespan. Issue 41 (30th September 2021) - Kang, Biyu; Wang, Yiyi; He, Xiaotong; Wu, Yaling; Li, Xinye; Lin, Chuyuan; Chen, Qinghua; Zeng, Lingxing; Wei, Mingdeng; Qian, Qingrong
Abstract : The WS2 /NPC-2 composite was synthesized as a high performance anode material for SIBs. Abstract : Sodium-ion batteries (SIBs) have been regarded as a promising substitute for lithium-ion batteries but there are still formidable challenges in developing an anode material with adequate lifespan and outstanding rate performance. Transition metal dichalcogenides (TMDs) are promising anode materials for SIBs due to their high theoretical capacities. However, their severe volume expansions and low electronic conductivity impede their practical developments. In addition, the synthesis of energy storage materials from waste biomass has aroused extensive attention. Herein, we synthesize WS2 nanocrystals embedded in N and P co-doped biochar via a facile bio-sorption followed by sulphurization, employing waste chlorella as the adsorbent and bio-reactor. The WS2 nanocrystals are beneficial for storing more sodium ions and expediting the transportation of sodium ions, thus improving the capacity and reaction kinetics. Chlorella acts as a reactor and not only inhibits the stacking of WS2 nanocrystals during the synthesis process but also alleviates the mechanical pressure of composite during the charge/discharge process. As a result, the WS2 /NPC-2 electrode delivers a high specific capacity (436 mA h g −1 at 0.1 A g −1 ) and superior rate performance of 311 mA h g −1 at 3 A g −1 for SIBs. It also exhibits excellent stability even up to 6000 cycles at 5 A g −1, which is one of the optimal long-cycle properties reported for WS2 -based materials to date.